The importance of foreign spectators’ expenditure in the tourism impact of mega-sporting events - Barget, Eric; Gouguet, Jean-Jacques (Papeles de Europa, 2012)
Many economic impact studies assessed that mega-sporting events can have aninfluence on the level of economic activity of the host territory. The attraction of manytourists is usually at the centre of the analysis. During the Rugby World Cup 2007 inFrance, foreign spectators are at the root of most of the economic impact on Frenchregions, with significant differences depending on their nationalities and their sociodemographicprofiles. It thus appears that the regional impact of the event is evenstronger since the host matches have attracted many foreign spectators with a highlevel of income and expenditure.